THU0401 The Frequency of Sacroiliitis and Spondylarthritis in Patients with Sarcoidosis. (10th June 2014) - Kobak, S.; Sever, F.; Ince, O.; Orman, M.
Abstract : Background: Sarcoidosis is a chronic granulomatous disease, which can involve different organs and systems. It can mimic or co-exist with various primary rheumatic diseases. Coexistence of sarcoidosis and spondyloarthritis has been reported in numerous case reports. Objectives: The purpose is to determine the incidence of sacroiliitis and spondyloarthritis in patients diagnosed with sarcoidosis, and to investigate any possible relation with clinical findings. Methods: Forty-two patients, who reffered to our rheumatology polyclinic between December 2011 and June 2013, and were diagnosed with sarcoidosis as a result of the examinations, were consecutively enrolled in the study. All findings were inquired in detail, and systemic and rheumatologic examinations were performed. Detailed investigation regarding spondyloarthritis was performed (inflammatory back pain, gluteal pain, uveitis, enthesitis, sausage fingers, inflammatory bowel disease, psoriasis, etc). Sacroiliac joint (SIJ) imaging in special positions for all cases and lateral heel imaging were performed. SIJ MRI was performed with STIR method to determine the existence of active sacroiliitis. All radiological reviews were evaluated by a radiologist experienced in musculoskeletal system radiology. Results: Sacroiliitis was found in 6 out of the 42 (14.3%) sarcoidosis patients. All the patients found to have sacroiliitis were female patients. While the average age of the cases found to have sacroiliitis was 55, the average duration of disease was 17.8 months. All six patients patients complained of inflammatory back pain. According to the staging of sarcoidosis, had stage 1 in two patients, and stage 2 in two patients, and stage 4 in two patients were specified. In radiological staging of sacroiliitis, stage 2 sacroiliitis was found in all six patients. When the patients were evaluated for HLA B-27, it was found negative in 6 patients. All the 6 patients with sacroiliitis were classified as spondyloarthritis according to the criteria of ASAS (Assessment of SpondyloArthritis international Society) and of ESSG (European Spondyloarthropathy Study Group). Conclusions: We found sacroiliitis and spondyloarthritis in patients with sarcoidosis at a percentage higher than in normal population. When we also take into account the genetic results (HLA-B27), the incidence of sacroiliitis in patients with sarcoidosis should be considered as a separate entity, rather than a common etiopathogenesis and/or a coincidental result. Controlled trials that involve large series of patients are needed for this. References: Pettersson T: Rheumatic features of sarcoidosis. Curr Opin Rheumatol 1998, 10:73–78. Gumpel JM, Johns CJ, Shulman LE. The joint disease in sarcoidosis. Annals of the Rheumatic Diseases 1967; 26: 194-205. Spilberg I, Siltzbach LE, McEwen C. The arthritis of sarcoidosis. Arthritis and Rheumatism 1969; 12:126-137. Smith JA, Marker-Hermann E, Colbert RA. Pathogenesis of ankylosing spondylitis: current concepts. Best Pract Res Clin Rheumatol 2006;20:571–91. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2052